The Importance of Facial Expression as Non-Verbal Communication in “A Man Called Otto” as Family Cinema Through: Semantics Analysis - Ahmad Al-Farisi, Nizar; Jaftiyatur Rohainiyah; Linta Wafdan Hidayah (Institut Agama Islam Negeri Palopo, 2025)
As human living in the world of communication, human intend to interact with other human being using both verbal and nonverbal communication. This study aims to describe the used of nonverbal communication and the importance of facial expression found in “A Man Called Otto” film, and find the meaning of facial expression used in this film. This research used descriptive qualitative with phenomenological approach to breakdown the effectivity of facial expression as nonverbal communication tools for humans to socialize with others. The finding of this research shows there are 7 types of Nonverbal communication were found, such as: kinesics, haptics, physical appearances, proxemics, environmental factors, paralanguage, and silence. After this finding, the researcher will focus on facial expression breakdown consist of 14 scenes from “A Man Called Otto” film. In this research, Students can benefit from this research by developing their analytical skills in interpreting facial expressions and their meanings within a narrative context. This can enhance their critical thinking and observational skills. And then, this finding can inspire students to conduct their own analyses of films or other media, focusing on non-verbal communication. This can lead to creative projects that explore how emotions are expressed visually.